(untitled) (Research, Society and Development, 2022)
Introduction: Cancer (CA) is one of the most terrible lethal diseases worldwide and the success of their current chemotherapy treatment strategies is limited due to several associated disadvantages, however, the researchers look for ways to improve the materials and produce new ones, in this study. Developed a bibliographic survey on the use of chitosan nanofibers as a biopolymer in the treatment of malignant neoplasms. Results and Discussion: Chemotherapy has become a predominant tactic for the majority of therapies, , but because it has many intense side effects, due to the potential to promote apoptosis, in cancer cells and in normal cells, thus presenting inherent limitations, it leads to the search for new strategies that solve the pH tolerance, low water solubility and intracellular diffusion in the delivery of drugs, with this, the chitosan demonstrates biocompatibility and has the ability to release sustained anticancer compounds, by being able to load drugs with reduced IC50 and synthetic agents, such as 5-FU, increase availability and effectiveness against CA. Conclusion: In short, the application of chitosan in chemotherapy contributes positively to its effectiveness and to alleviate its side effects.